Pelayanan Publik dan Kajian Putusan Korupsi Pengadaan Jasa Konstruksi dalam Perspektif Kontrak Jasa Konstruksi: Civil Engineering Perspective - Kombong, Eka Priska; Nugroho, Arief Setiawan Budi; Wibowo, Richo Andi (Komisi Pemberantasan Korupsi, 2020)
Infrastructure Availability such as government buildings, schools, hospitals are pivotal to underpin public services. The existence of infrastructure like irrigations, ports, roads, bridges, are also important to support social and economic activities of the people. However, the process of procurement in acquiring contractor may be tainted by corruption. This article examines various court decisions which have been final and binding. Three of the selected decisions are appealing to be discussed further, because it is doubted that the legal enforcers have been appropriately enforcing the law and understanding the context. On the first case, the legal enforcers have enforced the anti-corruption law to cases which are detrimental to the state finance. However, the substance of the cases is more suitably categorized as bribery or at least as gratification. On the last two cases, the legal enforcers have applied anti-corruption law for cases that cause the state financial loss. Nevertheless, from the perspective of civil engineering, whether the defendants were guilty are still debatable.